Funding developing Asia's old-age needs: Challenges and opportunities - Andrew Mason; Donghyun Park; Gemma Estrada (Asian Development Bank (ADB), 2024)
The population of developing Asia, in particular East Asia, is aging. Funding the needs of its growing population of older adults is the biggest socioeconomic challenge that aging presents for the region. The central objective of our paper is to analyze empirically how individuals fund their old-age needs in different economies. While developing Asian economies are the focus of our analysis, we also present results for high-income economies and non-Asian developing economies for comparative purposes. Our analysis relies heavily on wealth measures because these facilitate comparisons of flows over the life cycle, which vary strongly with age. Our analysis indicates that developing Asia's old-age funding needs will rise substantially because of population aging between 2025 and 2065. We find that labor income will play a smaller role in funding the region's old-age needs, while public and private transfers will play a larger role. While expanding public transfers will contribute toward old-age economic security, the region must carefully plan such expansion and avoid unsustainable generosity to safeguard the macroeconomic stability that underpinned its rapid economic growth and development.
Keywords: J11; J14; 330; aging; Asia; old-age economic security; public transfers